Analysis of Medical Legal Order as A Basis For Settlement of Medical Malpractice Disputes - I Nyoman Dwija Putra; Benjamin D Tungga; Cokorde's Istri Dian Laksmi Dewi (Indonesian Association for Public Administration (IAPA), 2021)
This study aims to determine whether the medical legal order can provide a solution for resolving medical disputes carried out by doctors against health service recipients in hospitals. The absence of a malpractice law creates confusion in decision making when doctors become involved in medical disputes. As primary legal material, is has a strong legal basis in making decisions on sanctions that can be imposed on doctors who commit malpractice by violating the professional code of ethics or working not according to standard operating procedures. The methods used are normative legar research methods and library legal research by conducting critical analysis on primary and secondy legal materials. The results of the study have shown that malpractice acts committed by doctors have a clear legal accountability mechanism ,as regulated in Health law number 36 of 2009, law number 29 of 2004 concerning medical practice.Administratively all forms of malpractice committed by docors can be threatened with criminal,civil,administrative sanctions an fines. At a more final level, administrative sanctions from malpractice acts committed by doctors can lead to on revocation of practice license.